Shaping Spatial Intelligence: The Influence of Curriculum on Students’ Spatial Ability - Husni, Niakmatul (Education, Science, and Technology International Conference, 2025)
Spatial ability plays a crucial role in mathematics and science learning, particularly in disciplines that require reasoning and problem-solving skills. The design of the curriculum significantly influences the development of students’ spatial ability. This study aims to analyze the impact of curriculum design on students’ spatial ability by comparing two curricula implemented in Indonesia: the 2013 Curriculum and the Merdeka Curriculum. A quantitative research approach was employed, involving 58 high school students majoring in science, with 27 following the Merdeka Curriculum and 31 following the 2013 Curriculum. Data were collected using a spatial ability test and analyzed using an independent two-sample t-test. The results indicate a significant difference in students’ spatial ability between the two curricula, with students following the Merdeka Curriculum outperforming those following the 2013 Curriculum. This suggests that a more flexible and exploratory learning approach, as emphasized in the Merdeka Curriculum, can enhance students’ spatial ability. The findings highlight the need for curriculum developers to integrate spatial reasoning into educational frameworks to improve students’ cognitive and academic development. Further research is recommended to explore the long-term impact of curriculum design on spatial ability and to examine other factors, such as teaching methods and socioeconomic background, that may influence spatial skills development.